THE RELATIONSHIP OF SPIRITUAL WELL-BEING AND ACCOUNTANT’S ETHICAL SENSITIVITY - Yuniarwati, Yuniarwati; Ardana, I Cenik; Dewi, Sofia Prima (Akuntansi Krida Wacana, 2018)
This study aims at determining the relationship of Spiritual Well-Being and the four dimensions of Spiritual Well-Being: Communal Well-Being, Personal Well-Being, Transcendental Well-Being, and Environmental Well-Being with Accountant’s Ethical Sensitivity. Sample is 49 accounting students who are preparing thesis. The research design is a correlational research. Data is collected using questionnaires and analyzed using Spearman correlation. The results show that Spiritual Well-Being is not correlated with Accountant’s Ethical Sensitivity. The correlation test of Spiritual Well-Being dimensions shows that Communal Well-Being, Personal Well-Being, and Transcendental Well-Being are positively correlated with Accountant’s Ethical Sensitivity, whereas Environmental Well-Being is not correlated with Accountant’s Ethical Sensitivity.Keywords: spiritual well-being, accountant’s ethical sensitivity, accounting student